The valuation of changes in commuting distances: An analysis using georeferenced data - Wolfgang Dauth; Peter Haller (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
We analyze the causal effect of commuting on wages, using a large sample of German job changers. Information on their home and workplace addresses in combination with road navigation software allows us to calculate exact door-to-door commuting distances with an unprecedented degree of precision. We use a theoretical model on spatial job search to motivate our empirical strategy. By focusing on job moves, we can use panel data techniques and control for unobserved individual heterogeneity. We find an asymmetric valuation of distance changes. Job changers value a reduction of their commuting distance higher than an increase. Apparently, individuals are not able to capitalize the full costs of commuting in their wages. A large part of this effect can be explained by sorting into certain firms at different distances and the rest by individual wage bargaining. – – In diesem Beitrag untersuchen wir den kausalen Effekt der Pendeldistanz auf das Tagesentgelt mit Hilfe eines großen Datensatzes von Arbeitsplatzwechslern in Deutschland. Wir nutzen "Navi-Software" und berechnen, anhand der geografischen Koordinaten von Wohnund Arbeitsorten, die genauen Tür zu Tür Pendeldistanzen mit dem PKW. Wir motivieren unsere empirische Strategie anhand eines theoretischen Modells der räumlichen Arbeitsplatzsuche. Durch den Fokus auf Arbeitsplatzwechsel beobachten wir dieselben Personen mehrmals, was uns erlaubt, für deren nicht beobachtbare Heterogenität zu kontrollieren. Die Ergebnisse zeigen eine asymmetrische Bewertung von Änderungen der Pendeldistanz. Nach einem Arbeitsplatzwechsel bewerten Personen eine Reduktion ihrer Distanz höher als eine Verlängerung. Dies deutet darauf hin, dass Arbeitnehmer nicht vollständig durch den Arbeitgeber für ihre Pendelkosten entschädigt werden. Ein Großteil des Effekts kann durch die Selbstselektion von Personen in bestimmte Firmen erklärt werden. Der Rest lässt sich auf individuelle Lohnverhandlungen zurückführen.
Keywords: J31; J64; R12; R40; 330; commuting; job search; marginal willingness to pay; loss-aversion